222k views
2 votes
Help plz thank you so much

Help plz thank you so much-example-1

2 Answers

2 votes

Answer:

x=0.73

Explanation:

(+16) 2x^2+12x-16= -3(+16)

2x^2+12x=13/12

2x^2= 1.08/2

x^2=.54

sqrt x^2=.54

x=0.73

User Talbot
by
5.3k points
6 votes

Answer:


x_1=-6.9\\x_2=0.9

Explanation:

The first step is to move all the terms from the right side to the left side of the equation and then add the like terms:


2x^2+12x-16=-3\\\\2x^2+12x-16+3=0\\\\2x^2+12x-13=0

Now we can apply the Quadratic formula. This is:


x=(-b\±√(b^2-4ac))/(2a)

In this case we can identify that:


a=2\\b=12\\c=-13

Finally, we must substitute these values into the Quadratic formula. Then we get:


x=(-12\±√(((12)^2-4(2)(-13)))/(2(2))


x_1=-6.9\\x_2=0.9

User Jkoestinger
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.